2018
DOI: 10.3389/fpls.2018.00824
|View full text |Cite
|
Sign up to set email alerts
|

The Making of Leaves: How Small RNA Networks Modulate Leaf Development

Abstract: Leaf development is a sequential process that involves initiation, determination, transition, expansion and maturation. Many coding genes and a few non-coding small RNAs (sRNAs) have been identified as being involved in leaf development. sRNAs and their interactions not only determine gene expression and regulation, but also play critical roles in leaf development through their coordination with other genetic networks and physiological pathways. In this review, we first introduce the biogenesis pathways of sRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 81 publications
1
34
0
Order By: Relevance
“…To test the effectiveness of the hundreds of STTMs that were generated, we subjected A. thaliana to large-scale transformation with STTMs, and scored the impact of STTMs on leaf development, root development, stature, and flowering. By observing different STTM transgenic lines in which different miRNAs were targeted, we found that miR156/157, miR160, miR165/166, miR167, miR171, miR319, miR159, and miR319/159 were involved in the development of leaf shape, as previously reported for some miRNAs (Allen et al, 2007;Todesco et al, 2010;Liu et al, 2011;Schommer et al, 2012;Yan et al, 2012;Yang et al, 2018) ( Figure 2A-2F and Supplemental Figure 1). STTM159 transgenic plants were smaller than wild-type (WT) plants and had upward curled leaves ( Figure 2B and .…”
Section: Multiple Developmental Phenotypes Observed In Arabidopsis Stsupporting
confidence: 82%
“…To test the effectiveness of the hundreds of STTMs that were generated, we subjected A. thaliana to large-scale transformation with STTMs, and scored the impact of STTMs on leaf development, root development, stature, and flowering. By observing different STTM transgenic lines in which different miRNAs were targeted, we found that miR156/157, miR160, miR165/166, miR167, miR171, miR319, miR159, and miR319/159 were involved in the development of leaf shape, as previously reported for some miRNAs (Allen et al, 2007;Todesco et al, 2010;Liu et al, 2011;Schommer et al, 2012;Yan et al, 2012;Yang et al, 2018) ( Figure 2A-2F and Supplemental Figure 1). STTM159 transgenic plants were smaller than wild-type (WT) plants and had upward curled leaves ( Figure 2B and .…”
Section: Multiple Developmental Phenotypes Observed In Arabidopsis Stsupporting
confidence: 82%
“…Leaf shape, size and anatomy are tightly controlled, both temporally and spatially, through complex gene regulatory networks. Many of them include the establishment of negative feedback loops between microRNAs and their targets allowing the formation of spatial domains locally controlling growth pattern along leaf morphogenesis ( Yang et al, 2018 ). While such systems confer sharp and robust boundaries to developmental processes, the multiplicity of the regulatory nodes involved offers many opportunities to fine-tune leaf morphology.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 10,714 potential targets for 176 miRNAs, with an average of 60.9 targets per miRNA (Table S14, Supplementary File S2). Family miR-396 had a larger number of targets (>9 targets for each family member), a fact also observed in Manihot esculenta [46] and Jatropha curcas [47].…”
Section: Microrna Targets Predictionmentioning
confidence: 52%
“…Although many studies have pointed out plant ncRNAs playing key roles in developmental [47,78] and regulatory processes [79,80], it is still uncommon to find studies identifying more than one or two ncRNA classes. Nevertheless, our analysis showed that, with several curation steps, it is possible to better assign most of the expected "housekeeping ncRNAs" and predict regulatory ncRNAs with high-confidence.…”
Section: Discussionmentioning
confidence: 99%